Adoption of paediatric and neonatal pulse oximetry by 12 hospitals in Nigeria: a mixed-methods realist evaluation. Issue 3 (26th June 2018) - Graham, Hamish R; Bakare, Ayobami A; Gray, Amy; Ayede, Adejumoke Idowu; Qazi, Shamim; McPake, Barbara; Izadnegahdar, Rasa; Duke, Trevor; Falade, Adegoke G
Abstract : Introduction: Pulse oximetry is a life-saving tool for identifying children with hypoxaemia and guiding oxygen therapy. This study aimed to evaluate the adoption of oximetry practices in 12 Nigerian hospitals and identify strategies to improve adoption. Methods: We conducted a mixed-methods realist evaluation to understand how oximetry was adopted in 12 Nigerian hospitals and why it varied in different contexts. We collected quantitative data on oximetry use (from case notes) and user knowledge (pretraining/post-training tests). We collected qualitative data via focus groups with project nurses ( n=12) and interviews with hospital staff (n=11). We used the quantitative data to describe the uptake of oximetry practices. We used mixed methods to explain how hospitals adopted oximetry and why it varied between contexts. Results: Between January 2014 and April 2017, 38 525 children (38% aged ≤28 days) were admitted to participating hospitals (23 401 pretraining; 15 124 post-training). Prior to our intervention, 3.3% of children and 2.5% of neonates had oximetry documented on admission. In the 18 months of intervention period, all hospitals improved oximetry practices, typically achieving oximetry coverage on >50% of admitted children after 2–3 months and >90% after 6–12 months. However, oximetry adoption varied in different contexts. We identified key mechanisms that influenced oximetry adoption in particular contexts. Conclusion: Pulse oximetry is a simple, life-saving clinical practice, but introducing it into routine clinical practice is challenging. By exploring how oximetry was adopted in different contexts, we identified strategies to enhance institutional adoption of oximetry, which will be relevant for scale-up of oximetry in hospitals globally. Trial registration number: ACTRN12617000341325.